Motywacja do nauki języka angielskiego w drugiej klasie szkoły podstawowej - Baran-Łucarz, Małgorzata (Neofilolog, 2017)
The main aim of this paper is to report the outcomes of a questionnaire study diagnosing children’s level of motivation to master English and its potential correlates, conducted among 78 primary school second graders attending one of the biggest public primary schools in Wrocław, Poland. The presentation of results is preceded by a brief overview of motivation models in SLA and analysis of earlier theoretical discussions and research in this area. The data suggest that the motivation level of the participants was high. Interestingly, the internal factors were found to be stronger correlates of motivation intensity (r = .68) than external factors (r = .40/ r = .42). More specifically, the factors most strongly related to motivation were as follows: integrative motives (r = .67), L2 user self-perception (r = .58) and aesthetic assessment of the target language (r = .54).